Pengembangan Modul Perhitungan Rumus Kimia dan Persamaan Reaksi Berbasis Inkuiri Terstruktur dengan Tiga Level Representasi untuk Kelas X SMA atau MA - Mira Permata Sari; Minda Azhar (Edukimia, 2019)
Module of chemical formula and reaction equation with three levels representation based structured inquiry had been determined validity and practility. The research type was research and development (R and D). The development model was 4-D model the consist of 4 stages, namely: define, design, develop and disseminate. This research was limited to the stage of development, namely the validity and practicality tests. The research instruments were used  observation questionnaire, validity and practicality. The modul was validated by 5 validators. Practicality test was carried out by 2 chemistry teachers and 24 XI grade students of IPA 2 SMAN Basa Ampek Balai. Data of the validity and practicality test were analyzed using the cohen kappa formula. The average kappa moment of validity test was 0,93  with a very high validity category. The average kappa moment of teacher and student practicality were 0,88 and 0,91 respectively with category very high practicality category. Thus, module of chemical formula and reaction equation with three levels representation based structured inquiry was valid and practice.